2015 IEEE International Advance Computing Conference (IACC) 2015
DOI: 10.1109/iadcc.2015.7154750
|View full text |Cite
|
Sign up to set email alerts
|

Resource allocation in cloud computing using agents

Abstract: In cloud computing scenario, efficiency of application execution not only depends on quality and quantity of the resources in the data center, but also on underlying resource allocation approaches. An efficient resource allocation technique is necessary for building an efficient system. The objective of this work is to propose an agent based Best-Fit resource allocation scheme which increases utilization of the resources, lowers the service cost and reduces the execution time. The work employs two types of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Genetic algorithm was modified to balance the load and to reduce the execution time and cost. An agent based best fit resource allocation scheme was proposed to increase the resource utilization [35]. The results showed that the best fit approach was better in terms of job execution time, cost, virtual machine allocation and resource utilization.…”
Section: Related Workmentioning
confidence: 98%
“…Genetic algorithm was modified to balance the load and to reduce the execution time and cost. An agent based best fit resource allocation scheme was proposed to increase the resource utilization [35]. The results showed that the best fit approach was better in terms of job execution time, cost, virtual machine allocation and resource utilization.…”
Section: Related Workmentioning
confidence: 98%
“…By this tactic, resource allocation advance to provision the sensitive deadline leases by decreasing the denial of the lease, in discrepancy to dual current algorithms via Haizea. Correspondingly, Shyam and Manvi [30] propose an efficient resource allocation scheme using cloud provider's resource agent and cloud user's task agent in IaaS Cloud. With maximizing the resource utility, reducing the total cost, and preserving the QoS, the minimum usage of the amount of VMs is ensured.…”
Section: Artificial Intelligent Resource Allocationmentioning
confidence: 99%
“…It is frequently generated to execute certain tasks by software competition ways or hardware virtualization techniques that are different than tasks are executed in a host environment. An-ping and Chun-xiang [31] Li and Li [34] Liang et al [33] Panda and Jana [29] Radhakrishnan and Kavitha [32] Shyam and Manvi [30] Vernekar and Game [35] Wang et al [36] Ali et al [44] Dai et al [48] Hu et al [45] Hadji and Zeghlache [49] Oddi et al [46] Saraswathi et al [39] Teng and MagoulFs [54] Wang and Liu [50] Wang and Su [40] Wolke and Ziegler [41] Wuhib et al [51] Wuhib et al [55] Xie and Liu [42] Xiao et al [47] Yin et al [52] Zhang et al [43] Zhang et al [ Ali et al [44] Dai et al [48] Hu et al [45] Hadji and Zeghlache [49] Oddi et al [46] Saraswathi et al [39] Teng and MagoulFs [54] Wang and Liu [50] Wang and Su [40] Wuhib et al [51] Wuhib et al [55] Xie and Liu [42] Xiao et al [47] Yin et al [52] Zhang et al [43] Zhang et al [53] Gu et al [65] Mashayekhy et al …”
Section: Analysis Of Resources and Parameters Used In Current Studiesmentioning
confidence: 99%
“…To address the issue mentioned above, many scheduling techniques have been proposed, with focus on enhancing multiple parameters simultaneously [32,[55][56][57][58].…”
Section: Multi-objective Scheduling Techniquesmentioning
confidence: 99%